The scientist in me 2 : worktext in science (Manila : Rex Book Store, Inc., 2019)
"The Scientist in Me series is specially designed to cater to the needs of the pupils to understanding the basic science concepts, to apply science-inquiry (science process) skills, and to exhibit scientific attitudes and values. Through this series, pupils will learn to solve problems critically and analytically. They will be able to make informed decisions and engage in discussions of relevant issues that involved Science, Technology, Engineering, and Mathematics (STEM)."
English text.